Gestión administrativa y su incidencia en la participación ciudadana del GAD municipal del cantón Valencia, año 2022. - López Cali, Andrea Carolina (2023)
Administrative management is a fundamental aspect in the functioning of any government entity, including municipal Decentralized Autonomous Governments (GAD). The way in which administrative management is carried out in this GAD has a direct impact on citizen participation and the quality of the services and programs provided to the community. The objective of this research project is to carry out an evaluation of the administrative management in 2022 of the Municipal GAD of Valencia and how this affects the citizen participation that applies. To carry out this research topic, the types of exploratory, descriptive and documentary research were used, this provided a comprehensive approach to understand administrative management and its influence on citizen participation. A survey aimed at citizens was carried out to collect information through standardized questions and an interview directed at the head of citizen participation about their perception in relation to citizen participation in administrative management. Relevant results were obtained the department of citizen participation implemented measures with the purpose of strengthening transparency in the administrative management of the Municipal GAD. 58% of citizens who participated in the survey expressed that the empty chair is the main method of citizen participation that requires immediate improvement. It shows both achievements and deficiencies in relation to the evaluation principles, this research can serve as a reference for future research where the topic is discussed.